Meningeal syndrome due to haemorrhage after lumbar puncture - Guimarães, Fernando (2007)
Lumbar puncture remains a useful and safe diagnostic test in many clinical situations. The most common complication associated with this procedure is lumbar puncture headache syndrome, which may include neck stiffness. Another frequent complication, usually without clinical relevance, is blood staining of the cerebrospinal fluid. We report here a case of meningeal reaction due to intrathecal haemorrhage after lumbar puncture. We discuss the delay in recognition of the situation, first assumed to be a post lumbar puncture headache, and differential diagnosis issues of blood stained cerebrospinal fluid.